Item-Based Acquisition of Dislocation in Early Child French - Jourdain, Morgane; Canut, Emmanuelle; Lahousse, Karen (Journal of Monolingual and Bilingual Speech, 2020)
This study tests whether the usage-based concept of item-based schema can explain the development of constructions other than verb-argument constructions (VACs). Through a corpus study of 600 dislocations produced by two French children between age 1;7.12 and 2;5.11, and 600 from their input, we show that the concept of item-based schemas can indeed be extended to other types of constructions. We also show that the earliest item-based schemas produced by children are similar to specific syntactic featuress of dislocations in their input, and that the dislocations produced by the adults of our corpus can also be described in terms of item-based schemas. Based on these results, we make the hypothesis that the dislocations of adults may not necessarily be produced based on a more abstract construction, and that the radical exemplar model developed by Ambridge (2019) could also explain our data.